Principles of voice quality theory: supralaryngeal settings and their effects on segmental production - Lee, Daniel Denian (Nanyang Technological University, 2023)
This thesis examines the theoretic relationships between voice quality settings and phonetic segments, undergirded by concepts expounded in Laver’s (1980) classic framework and building on the developments in Esling et al’s (2019) updated account. The investigation of voice quality presented in this thesis will be viewed through the lens of two foundational Laverian concepts: The principles of (1) SUSCEPTIBILITY and (2) COMPATIBILITY between settings and segments. As established in Laver’s seminal descriptions of voice quality, individual settings and segments are interdependent. Thus, the primary objective of this thesis is to explore the underlying nature of SETTING–SEGMENT interactions, through the employment of experimental magnetic resonance imaging (MRI) and acoustic data, to empirically ascertain the unique effects that particular settings have on specific segments. The voiced labiodental fricative /v/ and high back rounded vowel /u/ produced using a combination of various settings are analysed in this thesis. These segments are viewed against the backdrop of five voice quality settings: NEUTRAL (control), SPREAD LIPS, PROTRUDED LIPS, CLOSE JAW, and PROTRUDED JAW. The SETTING–SEGMENT permutations examined in this thesis are as follows: i) NEUTRAL: /v/, /u/ ii) SPREAD LIPS: /u/ iii) PROTRUDED LIPS: /v/, /u/ iv) CLOSE JAW: /v/ v) PROTRUDED JAW: /v/